Soil Health Management in Organic Production System – A Review - Shahane, Amit Anil; Shivay, Yashbir Singh (International Journal of Bio-resource and Stress Management, 2022)
At present, the soil is discussed in terms of the extent of degradation, increased pollution (footprint of human activity), and ecosystem services apart from the fertility and productivity point of view. To address these issues, soil needs to be defined in terms of its health. Healthy soil is the first and foremost entity in organic farming. In India, organic farming is spreading in areas subjected to different kinds of land degradation (hilly areas and semi-arid areas). Therefore, the study of soil health is important in organic farming. The article aims to discuss the concept of soil health and different agronomic interventions and management practices with their possible economics for maintaining soil health in an organic production system. The practices such as the use of biodynamic formulations, the use of microbial inoculations, and intercropping with leguminous crops have a positive effect on the nutrient supply besides improving soil health. The availability of a large array of options including input addition and management practices for soil health management provides potential for soil health management. Organic farming can afford the cost on soil health management considering its specification for organic sources, organic farming niche (North East India with high organic matter and semi-arid area with large bovine population), and premium prices of produce; while trade-off between premier prices and low yield in organic farming is well-defined constraint for investing of soil health at commercial scale in organic farming.